Treatise on Process Metallurgy, Volume 2 - Seetharaman, Seshadri (Elsevier, 2013)
Process metallurgy provides academics with the fundamentals of the manufacturing of metallic materials, from raw materials into finished parts or products.Coverage is divided into three volumes, entitled Process Fundamentals, encompassing process fundamentals, extractive and refining processes, and metallurgical process phenomena; Processing.